Early recruitment of PARP-dependent m8A RNA methylation at DNA lesions is subsequently accompanied by active DNA demethylation - Legartová, Soňa; Svobodová Kovaříková, Alena; Běhalová Suchánková, Jana; Polášek-Sedláčková, Hana; Bártová, Eva (RNA biology, 2022)
RNA methylation, especially 6-methyladenosine (m6A)-modified RNAs, plays a specific role in DNA damage response (DDR). Here, we also observe that RNA modified at 8-methyladenosine (m8A) is recruited to UVA-damaged chromatin immediately after microirradiation. Interestingly, the level of m8A RNA at genomic lesions was reduced after inhibition of histone deacetylases and DNA methyltransferases. It appears in later phases of DNA damage response, accompanied by active DNA demethylation. Also, PARP inhibitor (PARPi), Olaparib, prevented adenosine methylation at microirradiated chromatin. PARPi abrogated not only m6A and m8A RNA positivity at genomic lesions, but also XRCC1, the factor of base excision repair (BER), did not recognize lesions in DNA. To this effect, Olaparib enhanced the genome-wide level of γH2AX. This histone modification interacted with m8A RNAs to a similar extent as m8A RNAs with DNA. Pronounced interaction properties we did not observe for m6A RNAs and DNA; however, m6A RNA interacted with XRCC1 with the highest efficiency, especially in microirradiated cells. Together, we show that the recruitment of m6A RNA and m8A RNA to DNA lesions is PARP dependent. We suggest that modified RNAs likely play a role in the BER mechanism accompanied by active DNA demethylation. In this process, γH2AX stabilizes m6A/m8A-positive RNA-DNA hybrid loops via its interaction with m8A RNAs. R-loops could represent basic three-stranded structures recognized by PARP-dependent non-canonical m6A/m8A-mediated DNA repair pathway.
Keywords: RNA; DNA repair; oprava DNA; base excision repair; chromatin; PARP inhibitory; DNA Demethylation; DNA; Poly(ADP-ribose) Polymerase Inhibitors; DNA Repair; Chromatin; RNA methylation; epigenetics; DNA Methylation; metylace DNA; DNA demethylation; demetylace DNA; poškození DNA; DNA Damage